Screening Interpreting on the Social Construction of the Turkish in Economic Crisis 2025 - Rizka Ayuning Rosidi; Surwandono Surwandono (Jurnal Pemikiran Sosiologi, 2025)
The study is based on a paradoxical phenomenon: during a severe inflation crisis in 2025, with the annual rate reaching 35.41%, Turkish society appears to respond relatively calmly, showing no massive social turmoil or widespread protests. The economic pressure is significant, with the prices of necessities, housing, and utilities increasing sharply, eroding real purchasing power, and exacerbating inequality. This paradox raises the question of how Turkish society constructs its social reality under such economic stress. This study aims to understand this phenomenon through the lens of Peter L. Berger theory of social construction. Using a descriptive qualitative method, the research collects data through literature studies, media discourse analysis, policy document reviews, and in-depth interviews with workers, students, and community members in Turkey. The findings reveal that the Turkish government deliberately shapes social reality by restricting demonstrations, controlling narratives through mainstream media, and reinforcing nationalism as a unifying ideology. Through the stages of externalization, objectification, and internalization, the state produces an illusion of social stability which, in practice, masks forms of socio-political repression. Moreover, the rational-instrumental actions, such as adaptation to new prices and wage adjustments, and affective actions, such as pride in national identity, further contribute to society’s seemingly passive response. Overall, the study shows that the Turkish case is not merely about economic resilience but about how power constructs, directs, and sustains a dominant social reality during times of crisis.